Calorie Labelling on Menus: Are There Adverse Outcomes Related to Eating Disturbances? - Lillico, Heather (University of Waterloo, 2013)
Obesity is a serious health concern in Canada. Thirty-seven percent of the population are overweight and approximately 25% are obese. Increased energy intake from eating outside the home has contributed to the rise in obesity. Approximately one quarter of all Canadians consume food in a quick-service restaurant on a given day. Although not all food consumed outside the home is of poor nutritional quality, restaurants generally offer foods that have larger portions, and are higher in calories and fat. Menu labelling has the potential to promote healthier eating by informing consumers about the calorie content of meals. Currently, there is little or no research on possible unintended effects of displaying calorie information at restaurants and quick-service establishments. In particular, it is unclear how such information would affect individuals with clinical eating disorders, or those with eating disturbances. In the current study, 325 female undergraduate students over the age of 16 took part in a 10-minute paper-based survey after meal consumption in a cafeteria on the University of Waterloo campus. The study employed a pre-post design, with data collection occurring in paired and unpaired samples one month before calorie information was added to menu boards, and one week after. In the 299 participants with usable data the prevalence of eating disturbances (EAT-26 > 20) was 10.4%. Calorie consumption decreased from baseline (mean=678.2 kcal) to follow-up (mean=602.3 kcal; p=0.049). There were no statistically significant changes in any of the other outcomes from baseline to follow-up, including body image satisfaction, anxiety, mood, and frequency of engaging in unhealthy behaviours. Additionally, there were no interactions between eating disturbance level and time, which suggests that calorie labels did not differentially affect those in this high-risk population. Overall, no adverse outcomes related to eating disturbances were associated with the implementation of calorie labels in this at-risk population. The results have potential implications for menu labelling regulations.
Keywords: public health; eating disturbances; menu labels; Health Studies and Gerontology